ASSESSMENT OF COVID-19 RISKS RELATED TO BEHAVIOUR AND BODY RESISTANCE IN THE REMOTE AREA: CASE STUDY IN JENEPONTO - Basri, Basri; Ridjal, Andi Tilka Muftiah; Setiawan, Lukman; M, Renaldi (UI Scholars Hub, 2025)
COVID-19 has posed significant global health threats, with responses varying across populations due to differences in risk perception, behaviour, and biological vulnerability. In Indonesia, most research has focused on urban settings, with limited attention paid to rural or remote communities. This study assesses COVID-19- risks related—specifically behavioural and immunity-related-factors—in the remote area of both Bontoramba Subdistrict, Jeneponto Regency. A cross-sectional study was conducted using cluster random sampling across eight villages, with 183 participants selected from a total of 12,242 households. Data were collected between November to December 2020 using a validated structured questionnaire, administered both online and face-to-face interviews. The instrument assessed sociodemographic characteristics, in-home and out-of-home risk behaviours, and indicators of body resistance. Statistical analysis was performed using Chi-square tests to examine associations between demographic factors and risk-related behaviours. The majority of respondents were aged 30–39 years (62.3%) and employed in the private sector (62.8%). Key findings revealed high levels of moderate risk behaviour, particularly related to outdoor activity (80.9%) and public transport use (92.9%). Significant associations were found between gender, age, education, and occupation with various risk behaviours and body resistance indicators (p<0.05). Females generally practiced better in-home preventive behaviours, while males were more likely to engage in out-of-home risk behaviours. Younger individuals exhibited higher mobility and lower body resistance, while older respondents showed greater compliance with protective behaviours. Education and occupation also influenced risk patterns negatively. This study highlights the importance of considering sociodemographic contexts when designing public health interventions. Remote populations such as those in Bontoramba, face unique vulnerabilities due to behavioural exposure and limited physiological resilience. These findings underscore the need for targeted, context-specific health promotion strategies in similar rural settings.